Creation of the permanent inferior vena cava filter for prevention of pulmonary artery embolism - Yа.O. Povar; I.O. Skiba; B.M. Todurov; A.V. Khokhlov; I.V. Altman; V.M. Shivanyuk (Кардіохірургія та інтервенційна кардіологія)
The aim of the study was to create a new permanent cava filter to improve functional capacities of the construction and achieve high clinical parameters. A new geometry of the permanent inferior vena cava filter was presented which has high blood clot-capturing ability, does not cause thrombus fragmentation, makes migration impossible. The inferior vena cava filter does not injure the vessel wall and preserves integrity under long-term use. The inferior vena cava filter installation is safe and controllable, the filter self-positioning and reposition are possible, the delivery system size is 6F, the blood flow changing is minimal.